2018
DOI: 10.1051/matecconf/201814902071
|View full text |Cite
|
Sign up to set email alerts
|

Landslides susceptibility assessment using AHP method in Kanyosha watershed (Bujumbura-Burundi): Urbanisation and management impacts

Abstract: The Kanyosha watershed is unstable due to the presence of several landslides, which occupy about 3% of the study area. They are causing major damage which costs expensive to the Government of Burundi as well as to the population residing there and their properties. Roads, schools, irrigation canals, houses, crop fields, etc., are in danger of collapse. These landslides are mostly naturally occurring but can sometimes be reactivated by heavy rains or human activities during the excavation of building materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 8 publications
(3 reference statements)
5
16
0
Order By: Relevance
“…The geology is among the main controlling factor of landslides in the study area and in the region (Jacobs et al 2017;Kubwimana et al 2018). The spatial landslides distribution showed that most of the landslides occurred in outcrops within gneissic or granite units (Kubwimana et al 2018). To extract the lithological units, we digitalized the geological map of Burundi, Bujumbura sheet at 1/50000 (Laghmouch et al 2018).…”
Section: Lithologymentioning
confidence: 92%
See 4 more Smart Citations
“…The geology is among the main controlling factor of landslides in the study area and in the region (Jacobs et al 2017;Kubwimana et al 2018). The spatial landslides distribution showed that most of the landslides occurred in outcrops within gneissic or granite units (Kubwimana et al 2018). To extract the lithological units, we digitalized the geological map of Burundi, Bujumbura sheet at 1/50000 (Laghmouch et al 2018).…”
Section: Lithologymentioning
confidence: 92%
“…The slope angle controls landslides in the study area. Kubwimana et al (2018) showed that the slope angle controlled landforms in a central zone of the study area, the watershed of Kanyosha. In this study, we computed slope angle 10m DEM-based under ArcGIS 3D analysis tools.…”
Section: Slope Anglementioning
confidence: 98%
See 3 more Smart Citations